Cross Border Approach Sebagai Alternatif Model Kebijakan Pembangunan Kawasan Perbatasan - Saru Arifin (Fakultas Hukum Universitas Islam Indonesia, 2013)
This research rises the problems as follows: First, which factors contribute to the ineffective implementation of border area development policy. Second, whether Cross Border Approach model as relevant policy alternative will be implemented in the border area development and what pre-requisites are needed. This research used field survey method with interview, observation, and literature study techniques. The analysis model was conducted interactively. The findings conclude: First, the factors used in the development policy model by the government is less relevant with the area characteristics, including bureaucracy culture which is still sectoral, weak authority of border management board, inconsistency between technical policy and the border development paradigm, and isolated geographical condition which needs extra-ordinary treatment. Second, cross border approach is quite strategic to be policy model alternative for border development with some of its strength, among many, the program discussed is beneficial for both parties, the program is interest-based and the implementation is responded quickly by the government without undergoing complicated sectoral level.